GE_GERICHTE C/24586/2016 vom 15. Dezember 2017 - GE Cour de justice (2017)
BAIL À LOYER ; EXPULSION DE LOCATAIRE ; DÉFAUT DE PAIEMENT ; COMPENSATION DE CRÉANCES ; LOYER ; ABUS DE DROIT | CO.257d; CO.124; CO.270; CC.22;